Assessment of PM2.5 Patterns in Malaysia Using the Clustering Method - Ezahtulsyahreen Ab. Rahman; Firdaus Mohamad Hamzah; Mohd Talib Latif; Doreena Dominick (Aerosol and Air Quality Research)
Abstract Particulate matter is the parameter of most concern in air quality monitoring in Malaysia. This study discusses the variations and clustering of PM2.5 recorded from 2018 to 2019 at 65 stations of the Continuous Air Quality Monitoring Network of the Malaysian Department of Environment. PM2.5 concentrations were recorded continuously using a tapered element oscillating microbalance. The cluster analysis was conducted using the Agglomerative Hierarchical Cluster (AHC) method. The results show that the daily average of PM2.5 concentrations ranged between 8 and 31 µg m−3. The cluster regions were classified into High Pollution Regions (HPR), Medium Pollution Regions (MPR) and Low Pollution Regions (LPR) based on the AHC analysis. The mean concentration of PM2.5 recorded in HPR was significantly higher with 23.04 µg m−3 followed by MPR and LPR. The results also showed that the highest concentration of PM2.5 was recorded during the 2019 haze episode for all three regions, with the air pollutant index indicating very unhealthy and dangerous levels.